Research progress on vanadium oxides for potassium-ion batteries. (1st April 2023) - Wu, Yuhan; Chen, Guangbo; Wu, Xiaonan; Li, Lin; Yue, Jinyu; Guan, Yinyan; Hou, Juan; Shi, Fanian; Liang, Jiyan
Abstract: Potassium-ion batteries (PIBs) have been considered as promising candidates in the post-lithium-ion battery era. Till now, a large number of materials have been used as electrode materials for PIBs, among which vanadium oxides exhibit great potentiality. Vanadium oxides can provide multiple electron transfers during electrochemical reactions because vanadium possesses a variety of oxidation states. Meanwhile, their relatively low cost and superior material, structural, and physicochemical properties endow them with strong competitiveness. Although some inspiring research results have been achieved, many issues and challenges remain to be further addressed. Herein, we systematically summarize the research progress of vanadium oxides for PIBs. Then, feasible improvement strategies for the material properties and electrochemical performance are introduced. Finally, the existing challenges and perspectives are discussed with a view to promoting the development of vanadium oxides and accelerating their practical applications.